N6‐Methyladenosine Demethylase FTO Contributes to Neuropathic Pain by Stabilizing G9a Expression in Primary Sensory Neurons. Issue 13 (27th May 2020) - Li, Yize; Guo, Xinying; Sun, Linlin; Xiao, Jifang; Su, Songxue; Du, Shibin; Li, Zhen; Wu, Shaogen; Liu, Weili; Mo, Kai; Xia, Shangzhou; Chang, Yun‐Juan; et al.
Abstract: Nerve injury‐induced change in gene expression in primary sensory neurons of dorsal root ganglion (DRG) is critical for neuropathic pain genesis. N 6 ‐methyladenosine (m 6 A) modification of RNA represents an additional layer of gene regulation. Here, it is reported that peripheral nerve injury increases the expression of the m 6 A demethylase fat‐mass and obesity‐associated proteins (FTO) in the injured DRG via the activation of Runx1, a transcription factor that binds to the Fto gene promoter. Mimicking this increase erases m 6 A in euchromatic histone lysine methyltransferase 2 ( Ehmt2 ) mRNA (encoding the histone methyltransferase G9a) and elevates the level of G9a in DRG and leads to neuropathic pain symptoms. Conversely, blocking this increase reverses a loss of m 6 A sites in Ehmt2 mRNA and destabilizes the nerve injury‐induced G9a upregulation in the injured DRG and alleviates nerve injury‐associated pain hypersensitivities. FTO contributes to neuropathic pain likely through stabilizing nerve injury‐induced upregulation of G9a, a neuropathic pain initiator, in primary sensory neurons. Abstract : This study explores the m 6 A epitranscriptional mechanism of neuropathic pain. Peripheral nerve injury produces the Runx1‐triggered FTO upregulation in the dorsal root ganglion (DRG). This upregulation contributes to nerve injury‐induced pain hypersensitivity through erasing Ehmt2 mRNA m 6 A, stabilizing Ehmt2 mRNA/G9a expression, and silencing mu opioid receptor expression in the injured DRG. FTO may be a new target for neuropathic pain treatment.